The age-related deficit in LTP is associated with changes in perfusion and blood-brain barrier permeability. - Kerskens, Christian; Lynch, Marina; Kelly, Aine (My University, 2012)
In view of the increase in the aging population and the unavoidable parallel increase in the incidence of age-related neurodegenerative diseases, a key challenge in neuroscience is the identification of clinical signatures which change with age and impact on neuronal and cognitive function. Early diagnosis offers the possibility of early therapeutic intervention, thus magnetic resonance imaging (MRI) is potentially a powerful diagnostic tool. We evaluated age-related changes in relaxometry, blood flow, and blood-brain barrier (BBB) permeability in the rat by magnetic resonance imaging and assessed these changes in the context of the age-related decrease in synaptic plasticity. We report that T2 relaxation time was decreased with age; this was coupled with a decrease in gray matter perfusion, suggesting that the observed microglial activation, as identified by increased expression of CD11b, MHCII, and CD68 by immunohistochemistry, flow cytometry, or polymerase chain reaction (PCR), might be a downstream consequence of these changes. Increased permeability of the blood-brain barrier was observed in the perivascular area and the hippocampus of aged, compared with young, rats. Similarly there was an age-related increase in CD45-positive cells by flow cytometry, which are most likely infiltrating macrophages, with a parallel increase in the messenger mRNA expression of chemokines IP-10 and MCP-1. These combined changes may contribute to the deficit in long-term potentiation (LTP) in perforant path-granule cell synapses of aged animals
PUBLISHED
Keywords: Microglial activation; Long-term potentiation (LTP); Age; magnetic resonance imaging (MRI); blood-brain barrier (BBB); Hippocampus; T2 relaxation time; Perfusion imaging; Microglial activation; Long-term potentiation (LTP); Age; magnetic resonance imaging (MRI); blood-brain barrier (BBB); Hippocampus; T2 relaxation time; Perfusion imaging; Ageing; Neuroscience